Islamic Religious Pedagogy and Affective Literacy: Constructing Socio-Emotional Education Frameworks - Ana Mustaghfiroh; Umar Manshur; Muhammad Syahrul Mubaroq (Nurul Jadid University, 2025)
The demand for socio-emotional competencies in education increasingly emphasizes the importance of integrating affective literacy into Islamic pedagogy. This study aims to develop a framework for socio-emotional education grounded in Islamic values by examining affective literacy practices in religious learning. Using a qualitative case study design, data were collected through interviews with teachers and students, classroom observations, non-formal activities, and document analysis. These data were then analyzed through data condensation, display, and verification. The results of the study show three main findings: first, Islamic pedagogy is successfully integrated with affective literacy by linking verses and hadiths to students' emotional experiences; second, non-formal activities function as a socio-emotional laboratory to train empathy, patience, and cooperation; third, these practices produce a comprehensive framework that includes Qur'anic values, reflective learning, non-formal practices, and ongoing development. This study contributes by offering an Islamic alternative to the Western Social-Emotional Learning (SEL) model. This study recommends the application of an Islamic-based socio-emotional framework to strengthen moral and emotional intelligence in various educational institutions.